Effects of Adaptive Servo-Ventilation on Nocturnal Ventricular Arrhythmia in Heart Failure Patients With Reduced Ejection Fraction and Central Sleep Apnea–An Analysis From the SERVE-HF Major Substudy - Fisser, Christoph; Gall, Lara; Bureck, Jannis; Vaas, Victoria; Priefert, Jörg; Fredersdorf, Sabine; Zeman, Florian; Linz, Dominik; Woehrle, Holger; Tamisier, Renaud; Teschler, Helmut; Cowie, Martin R.; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: The SERVE-HF trial investigated the effect of treating central sleep apnoea (CSA) with adaptive servo-ventilation (ASV) in patients with heart failure with reduced ejection fraction (HFrEF). Objective: The aim of the present ancillary analysis of the SERVE-HF major substudy (NCT01164592) was to assess the effects of ASV on the burden of nocturnal ventricular arrhythmias as one possible mechanism for sudden cardiac death in ASV-treated patients with HFrEF and CSA. Methods: 312 patients were randomised in the SERVE-HF major substudy (no treatment of CSA [control] versus ASV). Polysomnography including nocturnal ECG fulfilling technical requirements was performed at baseline, and at 3 and 12 months. Premature ventricular complexes (events/h of total recording time) and non-sustained ventricular tachycardia were assessed. Linear mixed models and generalized linear mixed models were used to analyse differences between the control and ASV groups, and changes over time. Results: From baseline to 3- and 12-month follow-up, respectively, the number of premature ventricular complexes (control: median 19.7, 19.0 and 19.0; ASV: 29.1, 29.0 and 26.0 events/h; p=0.800) and the occurrence of ≥1 non-sustained ventricular tachycardia/night (control: 18%, 25% and 18% of patients; ASV: 24%, 16% and 24% of patients; p=0.095) were similar in the control and ASV groups. Conclusion: Addition of ASV to guideline-based medical management had no significant effect on nocturnal ventricular ectopy or tachyarrhythmia over a period of 12 months in alive patients with HFrEF and CSA. Findings do not further support the hypothesis that ASV may lead to sudden cardiac death by triggering ventricular tachyarrhythmia.